2001
DOI: 10.1007/s004410000341
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-rich cells in gills and skin of an African lungfish, Protopterus annectens

Abstract: We used scanning electron microscopy, the vital dye DASPEI and an antibody to the inner mitochondrial membrane to study the presence and localisation of mitochondria-rich cells in the gills and skin (opercular, dorsal and ventral) of the lungfish Protopterus annectens in its free-swimming conditions and at the beginning of aestivation. In the free-swimming period, the gills were short and thick and the pavement cells were extremely large (30-40 microns). The mitochondria-rich cells, which were distributed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…The aforementioned presence of MR cells in both the dorsal and ventral skin of P. annectens (Sturla et al 2001) is in accord with these data. Because MR cells are also present in amphibian skin (Ehrenfeld et al 1989), our data complement the morphological findings of Sturla et al (2001Sturla et al ( , 2002 and their prediction of a "convergence of strategies" of osmoregulation and ionoregulation between lungfish and amphibians.…”
Section: Ion Uptake Continues In Airsupporting
confidence: 88%
See 2 more Smart Citations
“…The aforementioned presence of MR cells in both the dorsal and ventral skin of P. annectens (Sturla et al 2001) is in accord with these data. Because MR cells are also present in amphibian skin (Ehrenfeld et al 1989), our data complement the morphological findings of Sturla et al (2001Sturla et al ( , 2002 and their prediction of a "convergence of strategies" of osmoregulation and ionoregulation between lungfish and amphibians.…”
Section: Ion Uptake Continues In Airsupporting
confidence: 88%
“…Few studies have examined the skin of lungfish (e.g., Kitzan and Sweeney 1968;Sturla et al 2001Sturla et al , 2002. Graham (1997) reported that supradermal capillary density in P. annectens was comparable with the density in many frogs, in which the critical role of the skin for water uptake is firmly established (for reviews, see Toledo and Jared 1993;J酶rgensen 1997).…”
Section: Extrabranchial Route(s) Of Water Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies of teleost gills have described the morphological and functional characteristics of gill epithelial cells (Carmona et al, 2004). These cells participate in various functions, such as gas exchange, maintenance of blood acid-base balance and ionic regulation (Brown, 1992;Laurent et al, 1994aLaurent et al, , 1994bMoron & Fernandes, 1996;Fernandes et al, 1998;Goss et al, 1998;Sturla et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Because most O 2 uptake occurs from the air, branchial ventilation in lungfish need not be constrained by convection requirements for O 2 uptake. Consequently, the gill is ventilated by low volumes of water (Jesse et al, 1967) and this factor, coupled with the low surface area and high bloodto-water diffusion distances of the lungfish gill (Sturla et al, 2001), results in arterial P CO 2 values that are unusually high for fish (~20-30路mmHg) (Lenfant and Johansen, 1968;Perry et al, 2005). Thus, the respiratory status of lungfish is more suitable for using ventilation to regulate acid-base disturbances than is the case for water-breathing fish.…”
Section: Introductionmentioning
confidence: 99%